ANALISIS PENGEMBANGAN HOME INDUSTRI KERAJINAN PURUN DI KELURAHAN PALAM KECAMATAN CEMPAKA, KOTA BANJARBARU - IRMA LIYANAWATI; RIZALI RIZALI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study aims to determine the relationship of aspects of working capital, raw materials, labor and marketing to the development of the purun home industry. Respondents interviewed 10 craftsmen with data collection technique through interview, observation and documentation. The data analysis technique used is descriptive, namely the data presented in tabulation form and the persentage of each answer category is calculated and to find out the existence of independent variabels both free and bound without linking the relationship between these variables.This study shows that limited aspects of capital and unskilled labor influence the development of the purun craft home industry. The difficulty of capital lending requirements from related parties makes it difficult for craftsmen to manage it and the imbalance of skills among craftsmen hinders the production process.